Systematic review of the firefly genus Amydetes Illiger, 1807 (Coleoptera: Lampyridae), with description of 13 new species - Da Silveira, Luiz Felipe Lima; Mermudes, José Ricardo M. (Zootaxa, 2014)
A systematic review of Amydetes Illiger, 1807, based on examination of the type-material. We fix A. fastigiata Illiger, 1807 as the type-species of the genus; redescribe the genus and six out of eight species; describe 13 new species; and provide illustrations and a key to species. We place A. vigorsi Westwood, 1830 syn. n. and A. gorhami Kuntzen, 1912 syn. n. in synonymy with A. fastigiata; A. suturalis Pic, 1925 syn. n. and A. brasiliensis Pic, 1925 in synonymy with A. apicalis; and A. flavicollis Olivier, 1888 syn. n. in synonymy with A. lucioloides Olivier, 1888. We report the first record of Amydetes from Venezuela and Argentina, and establish more precise distributions of the studied species. We describe the circadian period of A. apicalis (diurnal), A. fastigiata and Amydetes bellorum sp. nov. (nocturnal) and discuss the circadian diversity of the genus. Fronto-clypeus, antenna, labrum, maxillary palpomere, prothorax, mesosternum, lanterns, abdominal segment VIII and terminalia were structures that provided important characters for delimitation and diagnosis of the species.